Using microbes as a key tool to unravel the mechanism of autophagy and the functions of the ATG proteins - Mauthe, Mario (Microb Cell, 2016)
The study of microbe infections has always been a very effective approach to unveil and dissect cellular pathways. Autophagy is not an exception. Although some of the breakthrough discoveries in the field were obtained using yeast, pathogens have been and still are a great tool to discover and characterize new molecular and functional aspects of autophagy. Research on pathogens has helped to acquire knowledge about selective types of autophagy and the assembly of the autophagy machinery, i.e the autophagy-related (ATG) proteins, but also about alternative cellular roles of this pathway, such as secretion. Finally, microbes have also served to discover and characterize unconventional functions of the ATG proteins, which are uncoupled from their role in autophagy. In our recent study, we have taken advantage of viruses as a screening tool to determine the extent of the unconventional functions of the ATG proteome and characterize one of them.